2020
DOI: 10.2147/ccide.s219705
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation Of The Effect Of Different Surface Treatments, Aging And Enzymatic Degradation On Zirconia-Resin Micro-Shear Bond Strength</p>

Abstract: The purpose of this study was to evaluate the effect of surface treatments on zirconia-resin bonding and the effect of aging on bond durability for one year. Method: Three hundred and twenty zirconia blocks were divided into 4 equal study groups. Group 1 (control): as-sintered, group 2: (GB): grit-blasted, group 3: (LAS): laser-etched, group 4: (SIE): selective infiltration etching. Composite cylinders were bonded to the zirconia with resin cement and ceramic primer. Aging was performed following 3 different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The studies agree that the zirconia surface needs to be prepared before applying the resin cement since all the pretreatments increased the bond strength, improving the values of the control group [ 34 , 35 , 36 ]. The first requirement for adhesion is to achieve a surface free of contaminants.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The studies agree that the zirconia surface needs to be prepared before applying the resin cement since all the pretreatments increased the bond strength, improving the values of the control group [ 34 , 35 , 36 ]. The first requirement for adhesion is to achieve a surface free of contaminants.…”
Section: Discussionsupporting
confidence: 56%
“…Sandblasting with alumina particles improved the bond strength values due to the increase in surface energy, wettability, roughness, and the appearance of hydroxyl groups that will facilitate bonding with the primer/universal adhesive/cement [ 34 , 38 , 41 , 43 , 48 ]. The particle size used ranged from 30 to 110 µm, at 0.5–4 bar for 10–20 mm [ 30 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. An increase in particle size and pressure had long been associated with the formation of microcracks and weakening the mechanical properties of the material [ 35 , 39 , 41 , 49 , 58 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all aforementioned studies, only mechanical treatment of the Y-TZP blocks or crowns was applied without chemical treatment, and the incubation periods were either short-24 h [17] and 60 days [16]-or long (one year) [24]. A minimum incubation period of six months for testing the bond strength durability of SARCs to zirconia is advocated, whereas shorter incubation periods might provide misleading results [20,21]. A long-term aging process (nine months water storage and 10,000 thermocycles) was also applied in our previous study conducted with an identical study design [6], but in contrast to the current study, it reported unsatisfactory retention strength values of the Lava Y-TZP crowns, which greatly differed between the SARCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have pointed to the fact that long-term water storage should be used to evaluate the durability of the bond between resin cements, including SARCs, and zirconia. A minimum incubation period of six months is advocated [20,21]. Combined long-term water storage and thermocycling are well-established artificial aging methods, which are mandatory to test the bond strength durability of SARCs to zirconia [22,23].…”
Section: Introductionmentioning
confidence: 99%